Analisis Rekah Tarik Lereng Sidewall Penambangan Blok Menyango Berdasarkan Reliabilitas Kemantapan Lereng Menggunakan Metode Finite Difference - Novandri Kusuma Wardana (PROMINE, 2020)
Probability analysis is method in geotechnical parameter to solve problem on the stability of the mining slope. It explains values of distribution parameters based on data type of laboratory test results and field investigations result as a back analysis of the mining slope. Sidewall slopes had sliding plane due to tension crack as wide as 18 cm with a length of 150 meters had potential failure, so back analysis of slope stability is needed. Condition of uncertainty the rock of the slope when the increase saturation level 23% so that it gives a greater water pore pressure. Slopes with a geometry of sidewall 10 m high and a single slope angle of 50 ° require redesign of a height of 7 meters and a single slope angle of 42 °. The results of FK calculations obtained for the IRA slope were 1.24 with a probability of failure of 23.12% and the overall slope with FK 1.31 with a probability of failure of 18.27%. The results of the distribution of random variables using Chi - Square obtained Normal and Lognormal distributions for sandstones, Normal and Exponential distribution for claystone, and Lognormal distribution for siltstone.